2014
DOI: 10.2807/1560-7917.es2014.19.20.20805
|View full text |Cite
|
Sign up to set email alerts
|

A low-cost, sustainable, second generation system for surveillance of people living with HIV in Spain: 10-year trends in behavioural and clinical indicators, 2002 to 2011

Abstract: 88.2% as did those with CD4 T-cell counts ≥350 (from 48.2% to 66.9%) and viral copies <200 (from 47.0% to 85.2%). HIV-infected people with hepatitis C virus RNA decreased from 36.0% in 2004 to 29.9% in 2011, while those with HBsAg remained stable at around 4.4%. Implementation of a low-cost, sustainable system for second-generation surveillance in people living with HIV is feasible. In Spain, the information obtained has helped to define and refine public health policy and document treatment effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…Several factors could have influenced these findings. First, the proportion of known HIV-infected individuals receiving cART in Spain has increased significantly over the last decade, and more patients have a fully suppressed HIV viral load, a less advanced CDC clinical stage, and higher CD4+ T-cell counts [21]. These factors are important, because the results of a randomized clinical trial show that continuous suppression of HIV with cART reduces not only the risk of new AIDS-defining conditions and death, but also the risk of non–AIDS-defining conditions including cardiovascular events [24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors could have influenced these findings. First, the proportion of known HIV-infected individuals receiving cART in Spain has increased significantly over the last decade, and more patients have a fully suppressed HIV viral load, a less advanced CDC clinical stage, and higher CD4+ T-cell counts [21]. These factors are important, because the results of a randomized clinical trial show that continuous suppression of HIV with cART reduces not only the risk of new AIDS-defining conditions and death, but also the risk of non–AIDS-defining conditions including cardiovascular events [24].…”
Section: Discussionmentioning
confidence: 99%
“…This possibility seems to be justified by the observation that although mortality trends for HIV-infected individuals in Spain declined significantly when the first years of the cART era are taken as the reference, this was mostly at the expense of HIV-monoinfected patients, since declines in mortality rates were not observed among HIV/HCV-coinfected patients [30]. It is important to mention that injection drug use has been—and remains so today—the predominant mode of HIV acquisition in patients with HCV antibodies in Spain [10, 21, 29]. In other words, these patients are not only at risk of AIDS-related and liver-related deaths, but they are also at risk of death related to lifestyle factors including substance use, accidents, and suicide [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We expected to find worse survival in low-medium household income districts which our Unit had previously observed using other neighbourhood deprivation indicators [ 29 ]. Indeed, a national survey in Spain showed that employment among HIV patients was low (45.8%) [ 58 ]. Additionally, some of responders in this survey were living in prison (3.0%), other closed facilities (5.0%) or were homeless (1.8%).…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, we reviewed the results from the hospital survey of HIV/AIDS infected patients, a second-generation surveillance system in people living with HIV coordinated by the National Centre of Epidemiology [30], and the reports of two Spanish national cohorts: the “Grupo de Estudio de Sida” (GeSIDA) [31] and the “Asociación Médica VACH de Estudios Multicentricos (AMVACH)” [32]. From these sources we obtained the percentage of patients with HCV antibodies.…”
Section: Methodsmentioning
confidence: 99%